2005
DOI: 10.4049/jimmunol.175.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cutaneous IL-10 on Resident Epidermal Langerhans’ Cells and the Development of Polarized Immune Responses

Abstract: Prolonged topical exposure of BALB/c mice to chemical contact and respiratory allergens stimulates, respectively, preferential Th1- and Th2-type responses with respect to serum Ab isotype and cytokine secretion phenotypes displayed by draining lymph node cells. We now report that differential cytokine secretion patterns are induced rapidly in the skin following first exposure to the contact allergen 2,4-dinitrochlorobenzene (DNCB) and the respiratory sensitizer trimellitic anhydride (TMA). TMA induced early ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 46 publications
1
33
1
Order By: Relevance
“…These results are consistent with a previous report showing that IL-12 can turn DNTB into a strong sensitizer (14). IL-10 secretion, which antagonizes LC migration and IL-12 priming of T cells (28), was slightly higher in ASC deficient mice, but the difference was not statistically significant and the very low levels observed may undermine the relevance of our finding. Hence, our results suggest but do not prove that the inflammasome may modulate the secretion levels of IL-10, which may in turn regulate T cell fate.…”
Section: Cytokine Profile In Tolerance Vs Sensitization In Mouse Lympcontrasting
confidence: 37%
“…These results are consistent with a previous report showing that IL-12 can turn DNTB into a strong sensitizer (14). IL-10 secretion, which antagonizes LC migration and IL-12 priming of T cells (28), was slightly higher in ASC deficient mice, but the difference was not statistically significant and the very low levels observed may undermine the relevance of our finding. Hence, our results suggest but do not prove that the inflammasome may modulate the secretion levels of IL-10, which may in turn regulate T cell fate.…”
Section: Cytokine Profile In Tolerance Vs Sensitization In Mouse Lympcontrasting
confidence: 37%
“…Skinresident dendritic cells are potent antigen-presenting cells and immunological sentinels that respond following allergen exposure by functional maturation and migration toward draining lymph nodes (Cumberbatch et al, 2005). Dendritic cells exhibit a unique ability to activate naive T cells depending on their maturational stage.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, it may affect the antigen-presenting function of Langerhans cells and dendritic cells, since IL-10 pre-treatment of antigen-presenting cells was found to promote T H 2 cell activation (De Smedt et al, 1997;Morel et al, 1997). Cumberbatch et al (2005) demonstrated that chemical contact allergens and respiratory allergens exert differential effects on the kinetics of Langerhans cell activation and migration as a result of a differential cutaneous induction of IL-10. They concluded that immediate-type allergens may induce a cytokine environment that promotes the activation of dendritic cells with the ability to drive a T H 2-type immune response that may lead to an immediate-type allergy.…”
Section: Discussionmentioning
confidence: 99%